The Profession of Arms: Ideological Codes and Dominant Narratives of Gender in the Canadian Military - Taber, Nancy (Atlantis)

(untitled) (Mount Saint Vincent University, 2009)
This article discusses the ways in which specific Canadian military policies work as boss texts that construct a gendered narrative of the military as a way of life. This narrative is perpetuated through the ideological codes of duty, honour, and service before self.